The role of Nurses to The Trans Population in access to Health Services in Primary Care (Research, Society and Development, 2022)
Objective: The objective was to analyze the role of nurses in the access of trans population at health services in primary care. Method: An integrative bibliographic review, with a qualitative analysis of the literature available in virtual libraries. A search was done at Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature on Health Sciences (LILACS) and Google Scholar databases, using the descriptors: Nursing care, LBGT community, transsexual, primary health care and nurse. Results and discussion: Nine articles were selected to compose the study. It was evident that there is a lack of knowledge about the Brazilian National Policy for Lesbians, Gays, Bisexuals, Transvestites and Transsexuals Health (PNSILGBT) among nurses in primary health care. When performing care, nurses should always be welcoming, respectful, empathetic and non-judgmental. It is up to the nurse to execute actions with the trans population, with information related to health promotion, including the rights guaranteed to them by the national health system (SUS), in a humanized and holistic way, thus ensuring dignified and quality care. Conclusion: The articles analyzed revealed the national situation of the role of nurses with trans population in accessing health services in primary care and showed unpreparedness of professionals and health services in primary care to work with this population and the practice of the PNSILGBT.